Notomicrus josiahi, a new species of Noteridae (Coleoptera) from Venezuela - Miller, Kelly B. (Zootaxa, 2013)
Notomicrus josiahi sp. n. is described from a stream in southern Venezuela. The species differs from others in the genus in 1) large size for the genus (1.48–1.53mm), 2) smooth, shiny dorsal surface with indistinct punctation and mircroretic-ulation, 3) distinct coloration with head and pronotum yellow and elytron bicolored with basal portion black and apical portion brown, and 4) distinctive male genitalia. A checklist of the valid, known species of Notomicrus is given.